Synthesis of the extracellular domain of GLP-1R by chemical and biotechnological approaches. Issue 37 (26th August 2022) - Szolomajer, János; Stráner, Pál; Kele, Zoltán; Tóth, Gábor K.; Perczel, András
Abstract : A 10–15 kDa, 3-disulfide-bridges containing protein domain is obtained by SPPS and is expressed in E. coli . Abstract : The extracellular domain of the glucagon-like peptide-1 receptor, GLP-1R, is responsible for the binding of GLP-1, and a handful of additional agonists (such as exenatide, lixisenatide, and liraglutide) used daily for treating type II diabetes mellitus. Lead discovery and optimization, however, require binding studies, which, in turn, necessitate the total synthesis of GLP-1R, comprising 108 residues. A protein domain of 10–15 kDa size could be obtained either by expression in E. coli or by ligating solid-phase peptide synthesis (SPPS)-made fragments. However, direct overexpression fails to give a properly folded protein, as GLP-1R forms an inclusion body, which fails to refold due to improper disulfide pairing. Several bacterial strains, constructs, and fusion partners were probed and it was found that only co-expression with MBP gave a 3D-fold allowing the native disulfide bond pattern formation. Some fusion partners can act as covalently linked or in situ chaperones for guiding the refolding of GLP-1R toward success. Therefore, the bottleneck to preparing GPCR extracellular domains is the correct pairing of the Cys residues. As a proof-of-concept model, nGLP1-R was made by SPPS to form the purified full-length polypeptide chain, subjected to self-guided or spontaneous Cys pairing. However, the formation of correct SS-pairs was lagging behind any protocol in use support, and the bottleneck of large-scale protein production relies on the risky step of proper refolding, which is sometimes possible only if a suitable fusion partner effectively helps and catalysis of the correct disulfide formation.